2014
DOI: 10.1111/pcmr.12279
|View full text |Cite
|
Sign up to set email alerts
|

The mutational burden of acral melanoma revealed by whole‐genome sequencing and comparative analysis

Abstract: Acral melanoma is a subtype of melanoma with distinct epidemiological, clinical and mutational profiles. To define the genomic alterations in acral melanoma, we conducted whole-genome sequencing and SNP array analysis of five metastatic tumours and their matched normal genomes. We identified the somatic mutations, copy number alterations and structural variants in these tumours and combined our data with published studies to identify recurrently mutated genes likely to be the drivers of acral melanomagenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 20 publications
8
108
0
Order By: Relevance
“…It confirmed the main mutational subgroups of BRAF, NRAS, NF1, and triple wild type, as well as highlighting the distinct heterogeneity and high mutational burden of melanoma (Cancer Genome Atlas, 2015). Subtypes not included in the TCGA but published elsewhere were uveal (Van Raamsdonk et al, 2010), acral cutaneous (Furney et al, 2014), and mucosal melanoma (Sheng et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…It confirmed the main mutational subgroups of BRAF, NRAS, NF1, and triple wild type, as well as highlighting the distinct heterogeneity and high mutational burden of melanoma (Cancer Genome Atlas, 2015). Subtypes not included in the TCGA but published elsewhere were uveal (Van Raamsdonk et al, 2010), acral cutaneous (Furney et al, 2014), and mucosal melanoma (Sheng et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…27 There have been recent conflicting reports on UVR signatures in sequenced acral melanomas. Some studies report no dominant UVR signature within acral melanomas 10,15,26 while other studies report a dominant UVR signature in cases of acral melanoma: one case report of whole-genome sequencing; 28 two of six cases of melanoma cell lines examined; 29 and one of two cases of whole-genome sequencing. 27 In our view, these findings probably relate to the case selection; some cases designated as arising from acral sites may have involved the non-acral surfaces of the hands or feet.…”
Section: Acral and Subungual Melanomas With A Dominant Uvr Signaturementioning
confidence: 99%
“…In previous exome and whole-genome sequencing studies, mutations per Mb in acral melanomas have been reported to range from 1.02 to 3.68 (5 cases), 15 1.95, 28 and 2.79 to 14 (two cases). 27 In contrast, the mean mutation rate of The Cancer Genome Atlas Network study, 20 which consisted entirely of cutaneous melanomas, was 16.8 mutations/Mb.…”
Section: Acral and Subungual Melanomas With A Dominant Uvr Signaturementioning
confidence: 99%
See 1 more Smart Citation
“…40 Cutaneous melanoma has a mutation rate of ~15 mutations/Mb, 41,42 while the somatic mutation rate in acral and mucosal melanomas is 5-10-fold lower. 43,44 Uveal melanomas have the lowest mutational burden of any melanoma subtype. 45 Thus, mutational burden also generally parallels the reported ORRs for melanoma subtypes, though perhaps not as closely as PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%